Use of an Email Question and Answer Service to Characterize Vaccine Education Needs in the U.S. (4th October 2017) - Kroger, Andrew; Hughes, Lauren; Wolfe, Charles; Strikas, Raymond; Wing, Jessie; Johnson-DeLeon, M Suzanne
Abstract: Background: The Centers for Disease Control and Prevention (CDC) educates providers and the public about vaccine-preventable diseases and vaccines. Educational tools should be targeted to appropriate audiences and topic areas relevant to them. One important CDC educational tool is its long-standing email question and answer service, NIPINFO@cdc.gov. Two CDC public health professionals (one physician and one non-physician) are assigned daily to answer questions. We describe: 1) the distribution of queries by topic type, query source and level of difficulty; 2) analyses of questions involving safety, particularly safety of HPV vaccine; and 3) the impact of CDC introducing a new vaccine recommendation on the volume and type of queries related to that vaccine. Methods: Queries were summarized from August 2013 through March 2016. Queries were coded by topic (disease/vaccine), subtopic (e.g., safety), source (private provider, public provider, general public) and level of difficulty. Frequencies and strength of associations were generated by SAS 9.3. We also studied the trend of volume of queries relative to the timing of new CDC vaccine recommendations. Results: During the study period, 23, 783 queries were answered. The top three query topics were "multiple" (meaning one or more questions about more than one vaccine) (20%), influenza (14%), and miscellaneous (8%). HPV, miscellaneous, and multiple vaccine questions were most frequently rated the most difficult. The percentage of most difficult questions was similar among the public (10%) and providers (11%). HPV queries were more likely than non-HPV queries to be about safety (19% and 10% respectively P <.0001). HPV questions were more likely to come from the general public (31%) compared with other types of questions (20%). The timing of CDC vaccine policy publications did not affect the volume of questions received on that topic after the policy was published. Conclusion: The most common primary query topics were multiple vaccines, influenza, and miscellaneous. Safety of HPV vaccine is a topic that stimulates challenging questions. Publication of CDC vaccine recommendations did not affect timing or volume of queries in this evaluation. Disclosures: All authors: No reported disclosures.